Changing Design to Change Healthcare. (7th February 2023) - Gardien, Paul; Deckers, Eva
Abstract : Patients expect, especially after living through a global pandemic, far more personalized and tailored care that can only be delivered through a more decentralized healthcare system. A systemic approach is useful for addressing healthcare challenges in this era of major global challenges and may also provide a roadmap for other fields facing other complex, societal issues.